If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 9y = 3 Solving 7x + 9y = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9y' to each side of the equation. 7x + 9y + -9y = 3 + -9y Combine like terms: 9y + -9y = 0 7x + 0 = 3 + -9y 7x = 3 + -9y Divide each side by '7'. x = 0.4285714286 + -1.285714286y Simplifying x = 0.4285714286 + -1.285714286y
| 3+5(2-x)=2(x+4) | | y=19.66666667-7 | | 3-4x=111 | | 9x^2-12x=-5 | | -(1-3x)+4x=-15 | | (14x^2+6x+10)-(2x^2+8)= | | -8(-2m-8)+1=-31+4m | | y=.4x+1.2 | | -5x=-63+2x | | W=F(r+A) | | 1/3x=14 | | 26=5x+10+3x | | y=3+2*3 | | y=3+2*2 | | x/3=-20 | | 3(x+9)=4x-13 | | y=3+2*1 | | y=3+2*0 | | y=3+2*-1 | | y=3+2*-2 | | 4(-1)+y=-7 | | y=2+2*3 | | -22=d/17 | | y=2+2*2 | | 4(5+x)=5(4x-1)-23 | | y=2+2*1 | | log(x-2)+(x-5)=1 | | y=2+2*0 | | y=2+2*-1 | | y=2+2*-2 | | y=2+2x-1 | | 5z+2=0 |